Room temperature mechanical behaviour of cast in-situ TiAl matrix composite reinforced with carbide particles. (February 2019) - Lapin, J.; Štamborská, M.; Kamyshnykova, K.; Pelachová, T.; Klimová, A.; Bajana, O.
Abstract: Room temperature mechanical behaviour of cast in-situ TiAl matrix composite reinforced with carbide particles was studied using hardness, tensile, compression, and three-point bending tests. The initial microstructure of the in-situ composite consists of TiAl matrix reinforced with coarse primary (HTi2 AlC and TiC) and fine secondary (HTi2 AlC and PTi3 AlC) particles. The in-situ composite shows plastic deformation of TiAl matrix and limited plastic deformation of primary Ti2 AlC particles during the compression test. The compressive work hardening behaviour is affected by the plastic deformation of the matrix, plastic deformation of primary carbide particles and formation of cracks. The local equivalent strains in the compression specimens are numerically calculated using finite element analysis (FEA) and related to the size of primary carbide particles. The in-situ composite specimens show brittle fracture behaviour during tensile and three-point bending tests. The numerically calculated critical stress leading to a crack initiation in the notch tip region of three-point bending specimen is comparable with the ultimate tensile strength. The brittle fracture of the in-situ composite includes crack deviation, zone shielding by microcrack toughening, carbide fragmentation, delamination on the matrix-carbide interfaces and pull-out of the carbide particles from the matrix. Highlights: The hardness, fracture toughness, tensile and compressive properties are characterised. The effect of matrix and carbide particles on compressive work hardening behaviour is described. The compressive strains calculated by FEA are related to size of fragmented carbide particles. The critical stress leading to a crack initiation in notched specimen is calculated by FEA. The effect of coarse carbide particles on crack initiation and propagation is discussed.